Exploración de las condiciones institucionales de elementos de procuración de justicia en México - Montes Hernández, Ana Lilia (Archivos de criminología, seguridad privada y criminalística, 2023)
Public security is in the need to evolve constantly, the institutional conditions of the elements of law enforcement are a central axis to face the crime that currently occurs in Mexico and support the security. The objective of this research was to explore the conditions of the elements that are part of the institutions that are in charge of the administration of justice in Mexico. An investigation was carried out using quantitative methodology, with descriptive scope, cross-sectional and non-experimental design; a Google forms survey was conducted consisting of six exploration areas: institutional context, institutional development, use of the 911 system, participation in the processes, institutional perception, and self-care. This survey was sent to 145 people linked to law enforcement institutions. Through the results obtained, it is interpreted that the work carried out from the perspective of those who were surveyed is carried out in an adequate way and that there really are no eventualities that are significant to delimit the real problems of the institutional conditions that are presented in elements that have relationship with the administration of justice. It is concluded that the objective was fulfilled and that these institutional conditions should be studied further in subsequent research.